A New Removable Implant Analog - Flavio H. Rasetto, Odont, BDS, MS,1 and Carl F. Driscoll, DMD2 (Journal of Prosthodontics, 2003)
A new implant analog system that improves the efficiency of the implant restoration’s fabrication process is described.